Estudo comparativo entre controladores Fuzzy e PI para um sistema de tanque - Vieira, Felipe Bezerra (2017)
In the current industrial park, there is a number of problems with varied level of difficulty, one of the most recurrent is the control of levels of reservoirs or tanks. These systems contain some factors that hinder their control. One of the objectives of this work is the construction of various format tanks, which can impair the performance of classical controllers such as PID. One of the objectives of the work is a tank construction, a modeling test and thus building a simulator without Simulink®. The correct modeling has vital importance for the development of simulated systems, for poorly designed modeling invalidate this study and possible validation of controllers in the system. A comparative study will be made between classic control techniques and the Fuzzy controller, performing a comparison between the behavior of the controllers